PERAN GURU PPKn DALAM MENANGGULANGI MASALAH JUVENILE DELINQUENCY DI SEKOLAH - Sabiliun Muttaqina, Martines; Mona Adha, Mohammad; Sutrisno Putri, Devi; Nurmalisa, Yunisca; Hidayat, Karyadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the role of Civic Education (PPKn) teachers in addressing juvenile delinquency in schools. The research employed a qualitative method with a descriptive approach. The subjects of this study included PPKn teachers, principals, homeroom teachers, and students at SMAS Arjuna Bandar Lampung. Data were collected through interviews, observations, and documentation. Data analysis was conducted using triangulation techniques to ensure data credibility. The results indicate that PPKn teachers play a significant role in tackling juvenile delinquency through several strategies, including providing role models, integrating moral and ethical values in learning, fostering discipline, and collaborating with other school stakeholders and parents. In addition, personal approaches and guidance toward problematic students contribute to behavioral improvement. Therefore, it can be concluded that PPKn teachers have a crucial role in shaping students’ character and preventing juvenile delinquency in the school environment